Elite Capture of Foreign Aid: Evidence from Offshore Bank Accounts - Andersen, Jørgen Juel; Johannesen, Niels; Rijkers, Bob (Journal of Political Economy, 2022)
Do elites capture foreign aid? This paper documents that aid disbursements to highly aid-dependent countries coincide with sharp increases in bank deposits in offshore financial centers known for bank secrecy and private wealth management but not in other financial centers. The estimates are not confounded by contemporaneous shocks—such as civil conflicts, natural disasters, and financial crises—and are robust to instrumenting using predetermined aid commitments. The implied leakage rate is around 7.5% at the sample mean and tends to increase with the ratio of aid to GDP. The findings are consistent with aid capture in the most aid-dependent countries.